2014
DOI: 10.5194/acp-14-12181-2014
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric amines and ammonia measured with a chemical ionization mass spectrometer (CIMS)

Abstract: Abstract. We report measurements of ambient amines and ammonia with a fast response chemical ionization mass spectrometer (CIMS) in a southeastern US forest and a moderately polluted midwestern site during the summer. At the forest site, mostly C3-amines (from pptv to tens of pptv) and ammonia (up to 2 ppbv) were detected, and they both showed temperature dependencies. Aerosol-phase amines measured thermal-desorption chemical ionization mass spectrometer (TDCIMS) showed a higher mass fraction in the evening wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
151
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(158 citation statements)
references
References 66 publications
5
151
2
Order By: Relevance
“…Nitrate at the ensemble of Southeast sites averages 0.25 ± 0.08 µg m −3 in summer 2013, representing less than 4 % of PM 2.5 mass. Aerosol amines are present in low concentrations in the Southeast (You et al, 2014) and concentrations of alkaline cations other than ammonium (e.g., Ca 2+ , Mg 2+ ) are also too low to significantly affect the charge balance, as previously shown by Kim et al (2015). Concentrations of these other alkaline cations are reported at the CSN sites, and we find for the ensemble of CSN sites in Fig.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…Nitrate at the ensemble of Southeast sites averages 0.25 ± 0.08 µg m −3 in summer 2013, representing less than 4 % of PM 2.5 mass. Aerosol amines are present in low concentrations in the Southeast (You et al, 2014) and concentrations of alkaline cations other than ammonium (e.g., Ca 2+ , Mg 2+ ) are also too low to significantly affect the charge balance, as previously shown by Kim et al (2015). Concentrations of these other alkaline cations are reported at the CSN sites, and we find for the ensemble of CSN sites in Fig.…”
Section: Introductionmentioning
confidence: 48%
“…Here and elsewhere, mean ratios are calculated as the ratios of the mean quantities. ammonia concentrations at Southeast sites (You et al, 2014;Guo et al, 2015;Saylor et al, 2015;Weber et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the identities of these organics, and their abundance in the atmosphere, has remained an analytical challenge because of the inherent complexity of the chemical system, which involves a multitude of precursors and significantly more oxidation products (Bertram et al, 2009;Goldstein and Galbally, 2007). Chemical ionization mass spectrometry (CIMS) has become increasingly utilized for the measurement of these types of compounds (Bertram et al, 2011;Brophy and Farmer, 2015;Fortner et al, 2004;Hearn and Smith, 2004;Holzinger et al, 2010;Huey et al, 1995;Jokinen et al, 2012;Jordan et al, 2009;Lee et al, 2014;Lopez-Hilfiker et al, 2014;Slusher, 2004;Veres et al, 2008Veres et al, , 2010Yatavelli et al, 2012;You et al, 2014;Yu and Lee, 2012). Typically, a specific reagent ion is generated using a radioactive ion source, X-rays, or corona discharge, and then mixed with ambient air for a fixed time.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the strong evidence that sulfuric acid-amine nucleation is very efficient, it has rarely been observed in the atmosphere. Only one study has so far reported sulfuric acid-amine nucleation (Zhao et al, 2011) despite amine mixing ratios of up to tens of parts per trillion volume at some sites (Yu and Lee, 2012;You et al, 2014;Freshour et al, 2014;Yao et al, 2016). A global modeling study of sulfuric acid-amine nucleation has been carried out so far (Bergman et al, 2015), applying a nucleation parametrization based on the measurements of Almeida et al (2013) and Glasoe et al (2015).…”
mentioning
confidence: 99%